2020
DOI: 10.1111/mec.15609
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia modulates prevalence and viral load of Culex pipiens densoviruses in natural populations

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Indeed, a specific strain of Wolbachia ( w Pip-IV) was associated with higher CpDV loads in ovaries of laboratory colonies ( Altinli et al., 2019b ) and a higher prevalence in nature compared to another w Pip type (i.e. w Pip-I) ( Altinli et al., 2020 ). w Pip induces cytoplasmic incompatibility, a conditional sterility in crosses between females and males infected with incompatible Wolbachia strains in Cx.…”
Section: Symbiont-symbiont Interactionsmentioning
confidence: 99%
“…Indeed, a specific strain of Wolbachia ( w Pip-IV) was associated with higher CpDV loads in ovaries of laboratory colonies ( Altinli et al., 2019b ) and a higher prevalence in nature compared to another w Pip type (i.e. w Pip-I) ( Altinli et al., 2020 ). w Pip induces cytoplasmic incompatibility, a conditional sterility in crosses between females and males infected with incompatible Wolbachia strains in Cx.…”
Section: Symbiont-symbiont Interactionsmentioning
confidence: 99%
“…Indeed, Chaturvedi et al (2018) found that populations along the eastern slope of the Sierra Nevada Mountains were more similar to each other genetically relative to populations in other parts of the range, suggesting a common lineage in this area. Alternatively, JcDV prevalence could be maintained by other site‐dependent factors such as interactions with endosymbionts (e.g., Wolbachia , Altinli et al, 2020; Shastry et al, 2022), or abiotic factors (Carlson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have discussed and well documented the negative effect of Wolbachia on RNA viruses in different insect models such as mosquitoes and Drosophila [73][74][75], although there have also been reports about Wolbachia enhancement of both RNA and DNA viruses [76][77][78]. It is worth mentioning that the negative correlation of Wolbachia with GpSGHV was observed only when Wolbachia density was high as the results show the absence of high density (> 10 3.7 ) GpSGHV infection with high-density Wolbachia infection (> 10 7.5 ).…”
Section: Discussionmentioning
confidence: 99%